Journal of structural geology (Oxford, New York, Pergamon Press., 1979)
Access available online from 1995-through ScienceDirect
Keywords: Geology, Structural -- Periodicals; Tectonique -- Périodiques.; Structurele geologie; Geologische Struktur; Zeitschrift; Strukturgeologie